Systematic review of the use of prophylactic dressings in the prevention of pressure ulcers - Clark, Michael (2014)
This systematic review considers the evidence supporting the use of prophylactic dressings for the prevention of pressure ulcer. Electronic database searches were conducted on 25 July 2013. The searches found 3026 titles and after removal of duplicate records 2819 titles were scanned against the inclusion and exclusion criteria. Of these, 2777 were excluded based on their title and abstract primarily because they discussed pressure ulcer healing, the prevention and treatment of other chronic and acute wounds or where the intervention was not a prophylactic dressing (e.g. underpads, heel protectors and cushions). Finally, the full text of 42 papers were retrieved. When these 42 papers were reviewed, 21 were excluded and 21 were included in the review. The single high-quality randomised controlled trial (RCT)and the growing number of cohort, weak RCT and case series all suggest that the introduction of a dressing as part of pressure ulcer prevention may help reduce pressure ulcer incidence associated with medical devices especially in immobile intensive care unit patients. There is no firm clinical evidence at this time to suggest that one dressing type is more effective than other dressing.